Effect of 67-years of manuring, fertilization and amendments on fractions of soil organic carbon, nutrient dynamics and yield sustainability in an acidic Alfisol - RAHAMAN, RIAJ; BISWAS, SUNANDA; MAHAPATRA, PRABHAKAR; MEENA, MAHESH C; DEY, ABIR; DAS, T K; SINGH, PRIYA; PATIL, KALYANI (The Indian Journal of Agricultural Sciences, 2024)
Amending a problem soil in addition to nutrient input is crucial for maintaining a healthy and productive soil in the long run. The study aimed at evaluating the long-term impact of manuring and fertilization with or without liming on different soil attributes and crop yield in an acidic Alfisol. Surface soil samples (0–15 cm) were collected from selected 7 treatments, viz. Control; N; FYM; ½(N+FYM)+PX/2+KY/2; NPK; NPK+L; and P(A-X)K(B-Y)+FYM+L of the Permanent Manurial Trial (PMT) of Birsa Agricultural University, Ranchi, after the harvesting of rainy (kharif) maize (Zea mays L.) at the 67th crop cycle (2023 and 2024) and assessed for various fractions of soil organic carbon (SOC), available nutrients and yield attributes. The experiment was laid out in a randomized block design (RBD) and replicated thrice. The treatments which received manures either alone or in combination with chemical fertilizers recorded significantly higher amount of all the fractions of SOC, available nitrogen and lower bulk density as compare to the unfertilized plot or treatment with inorganic alone. The study also revealed that, addition of lime helped maintaining an optimum pH level, enhanced microbial activities and nutrient availability in the soil leading to a higher crop yield. Therefore, integrated use of manures and fertilizers in addition to lime for a prolonged period would have significant positive impact on soil health and sustaining its productivity.